Large mining and its urban impact in the 21st century: The peri-urban land as a conflictive scenario in an intermediate city like Cajamarca - Vega-Centeno, Pablo (2025)
During the 20th century, industrial activities linked to the extraction of minerals gave rise to the implementation of settlements or urban neighborhoods as company towns. In the 21st century, mining projects have emerged that focus more on connectivity, which reduces the direct impact on the production of urban spaces. However, its effects on the urban economy can lead to important impacts on urbanization processes. This article analyzes how uncontrolled urban expansion, derived from large-scale mining activity, transforms peri-urban spaces in an intermediate city like Cajamarca: they become scenarios of conflict between rural and urban logic, with changes in land use through notarial means, outside of municipal regulations.